The Perception of Basic Education Teachers In Caçador on Sustainability and Human Rights (Global Journal of Human-Social Science, 2023)
This article presents a research report applied to basic education teachers of the public network of Caçador-SC regarding the perception, importance, mastery and applicability in the classroom of themes related to sustainability, human rights, Agenda 2030 and Sustainable Development Goals of the UN. Data were collected via online forms that were answered in the Google Forms tool, later the data were compiled and presented in graphs explained and compared based on the educational context of the researched region and Brazil. The research concluded that teachers still have little mastery of the researched topics and emphasize the need for greater appropriation by teachers on these subjects, in view of the growing need and demand in the labor market for professionals who have knowledge in areas from performance to environmental, social and corporate governance. The methodology adopted for data analysis was based on quantitative and qualitative analysis and aimed to understand the contradictions and coherences in the answers given by the teachers.
Keywords: sustainability; human rights; teachers; agenda 2030